Evolution of the Macrophage CD163 Phenotype and Cytokine Profiles in a Human Model of Resolving Inflammation - Betsy J. Evans; Dorian O. Haskard; Gregory Sempowksi; R. Clive Landis (Hindawi Limited, 2013)
Cantharidin skin blisters were examined over two days to model the acute and resolving phases of inflammation in human skin. Four blisters were created by topical administration of cantharidin (0.1% v/v) to the forearm of healthy volunteers, with IRB approval. Duplicate skin blisters were aspirated at 16 and 40 hours to model the proinflammatory and resolving phases, respectively. There was a significant increase in leukocyte infiltrate at 40 h with appearance of a "resolving macrophage" phenotype CD14+CD163+ by flow cytometry. Neutrophils acquired apoptotic markers at 40 h and were observed to be phagocytosed by macrophagic "Reiter's" cells. Multiplex cytokine analysis demonstrated that monocyte chemoattractant protein (MCP-1/CCL2), interleukin- (IL-) 6, IL-8/CXCL8, macrophage inflammatory protein (MIP1α/CCL3), MIP-1β/CCL4, tumor necrosis factor- (TNF-) α, and eotaxin (CCL11) were all significantly upregulated at 16 h compared with 40 h. In contrast, immunoregulatory transforming growth factor- (TGF-) β, macrophage-derived chemokine (MDC/CCL22), and interferon-inducible protein (IP-10/CXCL10) were significantly elevated at 40 h. Our results demonstrate that the phases of inflammation and resolution can be discriminated in a two-day model of dermal wound healing. This confirms and extends our understanding of wound repair in humans and provides a powerful research tool for use in clinical settings and to track the molecular benefits of therapeutic intervention.